THE STUDY OF FRACTIONATION OF WHEAT BRAN FERMENTATIVE HYDROLYSATE WITH AMBERLITE XAD-4 - Bakholdina L.A.; Sevodin V.P. (Техника и технология пищевых производств, 2015)
Studies on feruloyl-oligosaccharides show high efficiency of these molecules in the prevention of colon can-cer. Fractionation of hydrolysates of plant substrates on polystyrene adsorbents resulting in acquisition of feruloyl-oligosaccharides was described. Wheat bran cleared of starch and proteins were fermented, and the hydrolysate ob-tained was passed through a column with polystyrene adsorbent «Amberlite XAD-4». The column was successively washed with water, water-alcohol mixture (1:1) and alcohol for elution of mono/oligosaccharides, feruloyl-oligosaccharides and free ferulic acid, respectively. The quantitative content of bound and free ferulic acid in the fractions was determined using the method of Folin-Ciocalteu (in application to ferulic acid), and the quantitative content of free ferulic acid was determined with the help of capillary electrophoresis. Qualitative content of free and bound ferulic acid in the fractions was determined by TLC. It has been found that Amberlite XAD-4 fractionnates mono/oligosaccharides, feruloyl-oligosaccharides and free ferulic acid. Ethanol has shown itself more effective than methanol in elution of fractions of feruloyl-oligosaccharides and free ferulic acid. Water fraction contained a small amount of bound ferulic acid, water-alcohol fraction contained mainly bound ferulic acid, and alcohol fraction con-tained free ferulic acid. It has been also determined that ferulic acid and its derivatives are chromatographed during the first passage through the column. The evaporated fractions were analyzed by TLC on plates of Silicagel 60 F254. After exposure to ammonia vapors in the hydro alcoholic phase under UV light, spots acquired light green fluorescence, which corresponds to the description of feruloyl-oligosaccharides in literature.